Brain size expansion in primates and humans is explained by a selective modular expansion of the cortico-cerebellar system. (September 2019) - Smaers, Jeroen B.; Vanier, David R.
Abstract: Comparative variation in brain size is arguably one of the most dominant features of primate evolution. Enduring questions in this context comprise whether evolutionary changes in certain brain regions outpace changes in other regions, and to what extent such regional variation between species explains comparative variation in overall brain size. To answer this question, we investigate the tempo and mode of evolution of brain organization using the largest combination of brain regions and species analyzed to date (36 brain regions, together representing over 90% of overall brain size, across 17 anthropoid primates, including humans). Following studies suggesting that the expansion of the major constituent regions of the cortico-cerebellar system (CCS) predominantly explain human brain size expansion, we test whether the link between variation in the CCS and brain size is consistent across primates. Results indicate that the constituent brain regions of the CCS show the highest rates of evolution, demonstrate a significant modular pattern of evolution, and closely align with changes in overall brain size. This phenotypic structure is consistent across different taxonomic scales, suggesting that the evolution of anthropoid brain organization is underpinned by a stable genetic structure and is characterized by a conserved evolutionary trajectory towards the CCS. Results hereby suggest that the expansion of the CCS is the primary driver of brain expansion in anthropoid primates. These findings have fundamental implications for our understanding of the nature of primate and human cognition, and the genetic and developmental structure that underpins brain evolution.